2005
DOI: 10.1021/ja0482280
|View full text |Cite
|
Sign up to set email alerts
|

CH5+:  Chemistry's Chameleon Unmasked

Abstract: The nuclear vibrational wave function and zero-point vibrational energy of CH5(+) are calculated using quantum diffusion Monte Carlo techniques on an interpolated potential energy surface constructed from CCSD(T)/aug'-cc-pVTZ ab initio data. From this multidimensional wave function, the vibrationally averaged rotational constants and radial distribution functions for atom-atom distances within the molecule are constructed. It is found that the distributions of all 10 H-H distances are bimodal and identical. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 47 publications
4
65
3
Order By: Relevance
“…If we compare the values, obtained here with those reported by Thompson et al 10 we find that the present values are larger by 0.06-0.08 cm -1 . This would reflect somewhat smaller a These equilibrium rotational constants differ from those that were obtained directly from a minimization at the CCSD(T)/aug-cc-pVTZ level of electronic structure theory/basis setby less than 0.001 cm -1 .…”
Section: Rotational Constantssupporting
confidence: 71%
See 2 more Smart Citations
“…If we compare the values, obtained here with those reported by Thompson et al 10 we find that the present values are larger by 0.06-0.08 cm -1 . This would reflect somewhat smaller a These equilibrium rotational constants differ from those that were obtained directly from a minimization at the CCSD(T)/aug-cc-pVTZ level of electronic structure theory/basis setby less than 0.001 cm -1 .…”
Section: Rotational Constantssupporting
confidence: 71%
“…A third potential surface was developed independently by Thompson, Crittenden, and Jordan. 10 This surface is based on electronic energies and Hessians, evaluated at the CCSD(T)/aug′-cc-pVTZ level of theory/basis using GAUSSIAN 98. In contrast to the fits of Bowman and co-workers, this potential is constructed using the Shephard interpolation, within the GROW 2.2 package of Collins and coworkers.…”
Section: Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of CH 5 ions, the calculations provide clear evidence for a CH 5 + unit. As demonstrated in several theoretical studies, [21][22][23][24][25][26] and also confirmed by the interpretation of infrared spectra, [27][28][29][30][31][32] CH 5 + is best viewed as an H 2 + moiety bound to CH 3 by a threecenter bond, although the structure is thought to be highly fluxional. In line with previous calculations on CH 5 + (CH 4 ) nÀ1 clusters, [33] this description of the CH 5 + unit is maintained when methane molecules are added.…”
mentioning
confidence: 85%
“…The limitations of current techniques are highlighted by the case of CH + 5 , a molecular ion of considerable interest due to its lack of a classical structure 10 and as the prototypical non-classical carbocation. 11 The only published highresolution spectrum of CH + 5 was recorded by Oka and coworkers 12 in a liquid nitrogen cooled discharge of H 2 and CH 4 , and was identified by a process of elimination, by removing the known spectral lines of H + 3 , CH + 3 , C 2 H + 3 , HCO + , HCNH + , the Rydberg spectrum of H 2 , and strong lines of CH 4 that remained due to a slight asymmetry in the AC plasma.…”
Section: Introductionmentioning
confidence: 99%